TINGKAT PENGETAHUAN, PERSEPSI, PEREFERENSI KONSUMEN, DAN PERILAKU PENGGUNAAN GAS ALAM DI KOTA BOGOR - Hayati, Arina; Hartoyo, Hartoyo; Retnaningsih, Retnaningsih (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research analyzed family characteristics, knowledge, perception, preference, and behavior of natural gas utilization; analyzed correlation among research’s variables; and identified the variables that influenced the behavior of natural gas utilization in Tegal Gundil, Bogor City. This research involved 60 families who used natural gas. Data collected by interview with questionnaire and was analyzed by descriptive, Pearson correlation, and regression test. The results showed that mostly family had good knowledge and perception about natural gas. Mostly family prefer to natural gas compare to others fuels. Research results also showed that all of family used natural gas to cook every day. Knowledge and perception about natural gas correlated significant with mother’s education and family income. Knowledge correlated positive significant with perception. Meanwhile, behavior of natural gas utilization was influenced by husband’s work and amount of family member.